2019
DOI: 10.3390/antib8040049
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Immunoglobulin G1 Fc Sialylation on Backbone Amide H/D Exchange

Abstract: The usefulness of higher-order structural information provided by hydrogen/deuterium exchange-mass spectrometry (H/DX-MS) for the structural impact analyses of chemical and post-translational antibody modifications has been demonstrated in various studies. However, the structure–function assessment for protein drugs in biopharmaceutical research and development is often impeded by the relatively low-abundance (below 5%) of critical quality attributes or by overlapping effects of modifications, such as glycosyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 70 publications
(151 reference statements)
0
12
0
Order By: Relevance
“…An example of the profound effects attributed to different glycosylation across the entire IgG is shown in Figure 39 . 532 More targeted studies of glycoengineered forms of IgG showed that it is specifically the galactosylation of the 6′ mannose arm that influences both CH2 dynamics and function. 534 This finding was remarkably consistent with a parallel study that noted the effect specifically of a α(2–3) linked sialic acid on the 6′ mannose arm of the IgG glycan in destabilizing the CH2 domain.…”
Section: Current Uses Of Hdx-msmentioning
confidence: 99%
“…An example of the profound effects attributed to different glycosylation across the entire IgG is shown in Figure 39 . 532 More targeted studies of glycoengineered forms of IgG showed that it is specifically the galactosylation of the 6′ mannose arm that influences both CH2 dynamics and function. 534 This finding was remarkably consistent with a parallel study that noted the effect specifically of a α(2–3) linked sialic acid on the 6′ mannose arm of the IgG glycan in destabilizing the CH2 domain.…”
Section: Current Uses Of Hdx-msmentioning
confidence: 99%
“…At the molecular level, the key role of the Fc N-glycans is to stabilize the Fc moiety of the IgGs in an open horseshoe-like conformation that increases the IgG interactions with the various FcγRs [ 28 ]. One branch of the biantennary glycans, the α1,6 arm, interacts with the protein backbone of the C H 2 domain while the other arm, the α1,3 arm, is mobile in the space between the two C H 2 domains and interacts with the opposite N-glycan [ 29 ]. The length and composition of both arms influence flexibility of the C H 2 domains and the level of openness of the Fc moiety [ 30 ].…”
Section: Igg-fcγr Interactionmentioning
confidence: 99%
“…55 Sialylation, on the other hand, is considered undesirable because its presence has been linked to the closing of Fc binding sites on a therapeutic, thus decreasing the Fc receptor binding and overall effector functionality of a therapeutic. 57,58,64 For Amgevita™ and Imraldi™ there was an increase in the percentage of acidic variants relative to Humira®. The higher levels of acidic variants were likely caused by the relative increase in sialylated species.…”
Section: Physicochemical Propertiesmentioning
confidence: 96%
“…Biosimilars showing higher levels of acidic variants, due to the presence of terminal sialic acids, 63 have the potential for decreased proteolytic resistance and effector functionality. 57,58,64 To determine that the post translational modifications of a biosimilar should not preclude it from gaining approval, There multiple concentrations/dosages available for Humira®.…”
Section: Physicochemical Propertiesmentioning
confidence: 99%